Probabilistic Seismic Hazard Analysis Incorporating Monte Carlo Method in the Case of Adelaide Region - Bambang Setiawan (Indonesian Journal on Geoscience, 2017)
DOI: 10.17014/ijog.4.2.81-96A topic of seismic hazard analysis (SHA) is briefly elaborated. A probabilistic seismic hazard analysis (PSHA) is commonly used to assess the ground motion level expected with different likelihood at a rock site during a future seismic event. The Incorporating Monte Carlo method into PSHA in an intraplate region (i.e. Adelaide region) is an interesting topic to explore. The result of the analysis using this method is able to characterize the likelihood of seismicity in a targeted region. Furthermore, the results clearly display the seismic ground motions in term of peak ground acceleration and peak ground velocity in Adelaide region. The de-aggregation of the analysis suggests two expected severe events for the Adelaide City. The first expected event is an earthquake M5.2 from a distance of 15 km and 25 km from the city. The second expected one corresponds to an earthquake M6.6 occurring 85 km away from the Adelaide City. However, the results of this analysis must be treated carefully due to dubious seismic data catalogue for a relatively large seismic event in Adelaide region.